The Effect of Applying Non-Financial Dimensions of the Balanced Scorecard on the Financial Performance in the Jordanian Private Hospitals - Siam, Walid Zakaria; Hussein, Ala`a Naim (Archives of Business Research, 2022)
This study aims to identify the impact of the application of non-financial dimensions of balanced scorecard in Jordanian private hospitals on its financial performance. To achieve the objectives of the study, the researchers designed a questionnaire to collect data on the extent of application of non-financial dimensions of balanced scorecard (independent variable), as well as the use of the financial statements for representative hospitals for the two years (2020 and 2021) in order to measure financial performance (dependent variable) of these hospitals through the Return on Assets (ROA). The study population was all Jordanian private hospitals listed by the Ministry of Health in 2022 (61), a sample of which was selected (18) hospitals (30% of the study population). The questionnaires were distributed to the Directors general and the directors of the departments and accountants working in Jordanian private hospitals. The number of distributed questionnaires is (167), (144) valid questionnaires to the analysis, i.e. (86.2%) of distributed questionnaires. The study received to many results, including: The keenness of the administrations of private hospitals to apply the non-financial dimensions of balanced scorecard and to a high degree, that the application of the non-financial dimensions of the balanced scorecard reflects positively on its financial performance. The researchers presented many of recommendations, including: strengthening the functioning of Jordanian private hospital administrations to provide infrastructure elements that may contribute to the satisfaction of patients, escorts and revisers.